Pengaruh Penerapan Metode Snowball Throwing terhadap Hasil Belajar Pengetahuan Tari pada Pembelajaran Seni Tari di Kelas XI.MIPA SMA Negeri 1 Rambatan Kabupaten Tanah Datar - Sidya Werleam; Yos Sudarman (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to prove the influence of the application of snowball throwing on the learning outcomes of dance-cultural arts, namely by analyzing the influence of differences in higher learning outcomes after a learning treatment using the snowball throwing method in learning cultural-dance arts in class XI, MIPA-2 SMA Negeri 1 Rabatan, Tanah Datar Regency. This research uses quantitative type with quasi-experimental method. The population is all students of class XI of SMAN 1 Rambatan totaling 183, with a study sample drawn in a simple cluster on 32 students of class XI-MIPA-2 (being an experimental class) and 32 students of class XI-MIPA-4 (being a control class). Data collection techniques with tests and observations. The data analysis technique uses the analysis of the difference in class mean in the final test-test results at the end of learning. . Hypothesis testing was performed with a T-test using the SPSS version 16 program, to test differences in the mean significance of the final test results in the experimental class and control class. The test results proved that the calculated t value at a score of 7.625 proved to be greater than the table t at a score of 1.69552. So statistically the value of t counts > t of the table. The results of this test also proved significant because t count > t this table was accepted at a critical value in the T-table at df= 31 and a confidence level of 95%, or at an alpha level of 0.05. The conclusion of the results of this study is that there is a significant difference in dance knowledge learning outcomes between the use of the snowball throwing method and conventional discussion methods in dance learning in class XI.MIPA SMA Negeri 1 Rambatan, Tanah Datar Regency.'. This means that H1 is accepted and H0 is rejected.